O papel da linguística cognitiva na formação do professor de alemão como língua estrangeira: um estudo sobre o ensino da preposição alemã über com base em esquemas imagéticos e metáforas conceptuais. - Adriana Fernandes Barbosa (2015)
The Cognitive Linguistics comprehends the meaning of words as a cognitive process (LAKOFF AND JOHNSON, 1980; LAKOFF, 1987; BRUGMAN AND LAKOFF, 1988) in which the speakers bodily experience with the environment is of central importance for the development of the language. Therefore, the Cognitive Linguistics values the polysemy of prepositions and their evidently spatial dynamics (BELLAVIA, 2007). In order to investigate the teacher's relationship with the applicability of these linguistic and cognitive concepts for teaching prepositions, as well as their relevance to the teaching of German as a foreign language, this study consists of the application of exercises about the preposition über, which were developed based on the concepts of image schemes and conceptual metaphors. The application was conducted by five teachers during their German lessons in an undergraduate course, as well as at the language centre of a university in Belo Horizonte. The classes were videotaped and teachers were interviewed thereafter. As the results emerged, it became clear that the use of image schemes and conceptual metaphors for teaching the preposition über was well accepted by most of the teachers. The format of the exercises highly motivated teachers to use pictures and gestures to explain, not only the meanings of über, but also, some grammatical structures related to this preposition. In addition, the adoption of cognitive concepts and strategies for teaching prepositions did not force teachers to abandon their original class model. Instead, teachers adapted the exercises to their own pedagogical profile. Nevertheless, the analysis of the data proved that having some theoretical knowledge of Cognitive Linguistics is important to support teachers to better explore the image schemes and the conceptual metaphors that underlie the different meanings and uses of prepositions like über. The findings suggest that theoretical studies regarding cognition ought to be included in the German teachers education programs.